Київська Русь в дискусіях польських істориків міжвоєнного часу - Гриневич, Т. (Історіографічні дослідження в Україні, 2010)
В статті аналізуються погляди польських істориків міжвоєнного часу на проблеми історії Давньоруської держави.
Дослі джу ються особливості їх бачення державотворчих
процесів та взаємин між народами середньовічної Польщі та
Русі. Виявлено значний вплив політичного чинника на
формування польських візій проблем «норманізму» та ґенези
розбіжностей обох народів. Зроблено висновок про вагомість
проблематики історії Давньої Русі для польської міжвоєнної
історичної науки. In the article views of the Polish historians between two World
Wars on the problems of history of Ancient Rus have been analysed.
The peculiarities of their perception of the state — forming processes
and mutual relations between the peoples of medieval Poland and
Rus have been studied. The great influence of the political factor on
the formation of Polish studies in the problem of «normanism» and
the genesis of differences of two people has been revealed. The
conclusion about great importance of the problematics of Ancient
Rus for Polish history of the period between two World Wars has
been made.